Methods to Compare Predicted and Observed Phosphene Experience in tACS Subjects - Aprinda Indahlastari; Aditya K. Kasinadhuni; Christopher Saar; Kevin Castellano; Bakir Mousa; Munish Chauhan; Thomas H. Mareci; Rosalind J. Sadleir (Neural Plasticity)
Background. Phosphene generation is an objective physical measure of potential transcranial alternating current stimulation (tACS) biological side effects. Interpretations from phosphene analysis can serve as a first step in understanding underlying mechanisms of tACS in healthy human subjects and assist validation of computational models. Objective/Hypothesis. This preliminary study introduces and tests methods to analyze predicted phosphene occurrence using computational head models constructed from tACS recipients against verbal testimonies of phosphene sensations. Predicted current densities in the eyes and the occipital lobe were also verified against previously published threshold values for phosphenes. Methods. Six healthy subjects underwent 10 Hz tACS while being imaged in an MRI scanner. Two different electrode montages, T7-T8 and Fpz-Oz, were used. Subject ratings of phosphene experience were collected during tACS and compared against current density distributions predicted in eye and occipital lobe regions of interest (ROIs) determined for each subject. Calculated median current densities in each ROI were compared to minimum thresholds for phosphene generation. Main Results. All subjects reported phosphenes, and predicted median current densities in ROIs exceeded minimum thresholds for phosphenes found in the literature. Higher current densities in the eyes were consistently associated with decreased phosphene generation for the Fpz-Oz montage. There was an overall positive association between phosphene perceptions and current densities in the occipital lobe. Conclusions. These methods may have promise for predicting phosphene generation using data collected during in-scanner tACS sessions and may enable better understanding of phosphene origin. Additional empirical data in a larger cohort is required to fully test the robustness of the proposed methods. Future studies should include additional montages that could dissociate retinal and occipital stimulation.